Pheretima javanica K. Ethanol Extract Granules’ Effects on Eosinophil Level, Immunoglobulin E Level, and Organs Histopathology in Rattus norvegicus B. - Dwi Wahyuni; Joko Waluyo; Jekti Prihatin; Fersty Isna Kusumawardani; Aditya Kurniawan (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Traditional medicine that might be useful to treat typhoid fever is earthworms (Pheretima javanica K.). It is important to know whether any substances contained in Pheretima javanica K. extract are toxic and have pharmacological effects, which can be observed from the eosinophil and immunoglobulin E (IgE) levels in the blood.METHODS: Thirty Rattus norvegicus B. were included in this study and were separated into 5 groups, with 6 rats in each group. T1, T2, T3, and T4 were groups of rats treated with 50, 300, 2000, and 5000 mg/kg BW of Pheretima javanica K. ethanol extract granules (PJEEG), respectively, while the control group was a group of rats treated with 0.36 mg Ciprofloxacin. The eosinophil number and the IgE concentration were detected. Physical observations were also conducted to detect any allergic symptoms, toxicity symptoms, or histopathological changes.RESULTS: Administration of PJEEG significantly increased the number of eosinophil in every group, from 49.82 cells/μL to 259.26 cells/μL on average (p<0.001). PJEEG did not significantly affect IgE levels (p=0.624). The results showed that the administration did not cause any allergic and toxicity symptoms. Histopathological analysis of rats’ kidneys and liver also showed that the administration had no significant effect on histopathological changes.CONCLUSION: The administration of PJEEG does not cause allergic symptoms, toxicity symptoms, and histopathological changes in rats. The administrations also significantly increase eosinophil number in rats’ blood. However, the concentration of IgE in rats’ blood was not significantly changed after administration of PJEEG.KEYWORDS: allergies, typhoid fever, earthworms, Pheretima javanica K., eosinophil, immunoglobulin E